The Future of Rural Public Accountants: To What Extent Can Technological Transformation Provide Solutions to the Village Fund Administration Service Sector - Hengky Leon; Lamhot Leonard Fitri; Muhammad Fadila Laitupa; Pandu Adi Cakranegara; Elna M Pattinaja (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study discusses the future of rural public accountants, which we focus on concerning technological transformation, which is a solution for village fund management work. Many rural public accounting studies have received attention. Still, few have studied it from the perspective of technology application transformation, a solution to public accounting problems at the village government level. Through the help of technological data search, this study has obtained much scientific evidence in the form of publications of public accounting studies and the effectiveness of digital applications in assisting village fund governance tasks as many understand that the government in Indonesia is certainly not free from problems with the ability to use technology to activate rural financial accounting work. We analyze the data we collect electronically to find solutions to problems related to the effectiveness of digital technology transformation to help with village fund accounting work. After a series of studies involving data coding systems, in-depth evaluation, and high interpretation, we can finally conclude that the future of accounting will continue to improve when the era of automation helps accounting professionals as today's technology in government offices in cities and industry will later through a digital transformation of the apparatus. In the village, through training and concern for the parties, the accounting profession will gradually be able to help with village fund management tasks. Many villages today continue to improve by employing human resources familiar with automation accounting application technology and the village's commitment to serving the community more professionally, especially the governance and village sections. Thus, it is hoped that these findings will become additional knowledge and experience for similar studies in the future.